Preface: Shakespeare and Shakespearean Influence in the Renaissance and Beyond - Najbauer, Noémi M. (FOCUS: Papers in English Literary and Cultural Studies, 2014)
The issue titled Shakespeare and Shakespearean Influence in the Renaissance and Beyond features papers on moments of intertextuality between a Shakespeare play and other works of literature, forms of adaptation of a Shakespeare play, irrespective of genre, aspects of the cultural-historical context in which Shakespeare lived and worked, and Shakespeare-based comparative studies by an array of contributors at various Hungarian universities.